Influence of varied sprouted barley feeding levels on carcass traits, meat quality, and fatty acid profile of lambs - Saleh Al-Ghamdi; Hani H. Al-Baadani; Abdulrahman S. Alharthi; Walid Soufan; Gamaleldin M. Suliman; Mutassim M. Abdelrahman; Ibrahim A. Alhidary (Cogent Food & Agriculture)
The aim of this study was to evaluate the carcass characteristics, meat quality and fatty acid profile of lambs fed different levels of sprouted barley (SB) compared to a control group fed a diet based on barley grain and alfalfa hay. Forty-five intact male Awassi lambs (3 months old) were included in the study and were fed for 75 days, divided equally into five feeding groups based on their average body weight. The groups were fed diets containing 25%, 50%, 75% and 100% SB replacing the control diet of barley grain and alfalfa hay (SB25, SB50, SB75 and SB100, respectively). The results showed that SB (SB25–SB75) had no effect on body weight gain while a significant gradual decrease in dry matter, crude protein and crude fat intake with the inclusion of SB (SB50–SB100). Higher rates of SB, especially 50%, 75% and 100%, resulted in a remarkable decrease in body wall fat. In addition, the treatment groups receiving SB50, SB75 and SB100 had a significantly lighter ultimate meat color compared to the control diet (p < 0.05). Interestingly, lambs fed SB25 resulted in the lowest saturated fatty acids and the highest mono-unsaturated fatty acids compared to the control group. In conclusion, partial replacement of the basal diet with SB can improve growth performance, carcass characteristics, body fat distribution and fatty acid profile of lambs. Therefore, further studies are needed to verify the optimal use of SB as one of the feeding systems to increase the nutritional requirements of growing lambs.